A synthesis of methane dynamics in thermokarst lake environments - Heslop, J. K.; Anthony, K. M. Walter; Winkel, M.; Sepulveda-Jauregui, A.; Martinez-Cruz, K.; Bondurant, A.; Grosse, G.; Liebner, S. (My University, 2020)
Greenhouse gas emissions from physical permafrost thaw disturbance and subsidence, including the formation and expansion of thermokarst (thaw) lakes, may double the magnitude of the permafrost carbon feedback this century. These processes are not accounted for in current global climate models. Thermokarst lakes, in particular, have been shown to be hotspots for emissions of methane (CH4), a potent greenhouse gas with 32 times more global warming potential than carbon dioxide (CO2) over a 100-year timescale. Here, we synthesize several studies examining CH4 dynamics in a representative first-generation thermokarst lake (Vault Lake, informal name) to show that CH4 production and oxidation potentials vary with depth in thawed sediments beneath the lake. This variation leads to depth-dependent differences in both in situ dissolved CO2:CH4 ratios and net CH4 production responses to additional warming. Comparing CH4 production, oxidation, and flux values from studies at Vault Lake suggests up to 99% of produced CH4 is oxidized and/or periodically entrapped before entering the atmosphere. We summarize these findings in the context of CH4 literature from thermokarst lakes and identify future research directions for incorporating thermokarst lake CH4 dynamics into estimates of the permafrost carbon feedback.
Keywords: methane; methane oxidation; permafrost carbon feedback; rapid thaw